2003
DOI: 10.1056/nejmoa025273
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Screening for Trisomies 21 and 18

Abstract: First-trimester screening for trisomies 21 and 18 on the basis of maternal age, maternal levels of free beta human chorionic gonadotropin and pregnancy-associated plasma protein A, and measurement of fetal nuchal translucency has good sensitivity at an acceptable false positive rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
150
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 531 publications
(163 citation statements)
references
References 22 publications
8
150
2
3
Order By: Relevance
“…16 cases of trisomy 21 (prevalence was 1 in 156 pregnancies) were found in present study and similar to result of Wapner et al [13] (1 in 135 pregnancies), but rather higher than reported by Leung et al [14] (1 in 334 pregnancies) in China, by Dhaifalah et al [15] (1 in 343 pregnancies) in Czech and by Theodoropus et al [16] (1 in 355 pregnancies) in Greece. This difference was depended on the efficacy of prenatal screening program and the risk of obstetrical study population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16 cases of trisomy 21 (prevalence was 1 in 156 pregnancies) were found in present study and similar to result of Wapner et al [13] (1 in 135 pregnancies), but rather higher than reported by Leung et al [14] (1 in 334 pregnancies) in China, by Dhaifalah et al [15] (1 in 343 pregnancies) in Czech and by Theodoropus et al [16] (1 in 355 pregnancies) in Greece. This difference was depended on the efficacy of prenatal screening program and the risk of obstetrical study population.…”
Section: Discussionsupporting
confidence: 91%
“…However, we didn't find out a significant correlation with trisomy 21 and the advanced of maternal age (OR = 2.45, p = 0.124) because our study was a low-risk study population (the means of maternal age was 28.9 ± 4.5 years); so it was not eligible to use the maternal age to evaluate the possibility of trisomy 21 in young obstetrical population. Furthermore, according to Nicolaides et al [1,19] maternal age screening had also a low detection rate (30%) for prediction of trisomy 21 and it also showed no advantage for using maternal age alone in comparison into the combined of fetal NT thickness and biochemical serum [13]. Similarly, Niemimaa et al [20] believed that trisomy screening by using of maternal age alone has a low detection rate and a high false positive rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-trimester screening (FTS) has been identified as an effective screen for trisomy 21 (Wapner et al, 2003;Avgidou et al, 2005) with detection rates of approximately 90% and low false positive rates were achieved Wapner et al, 2003). This technique uses fetal nuchal translucency (NT) and maternal serum markers of free beta-human chorionic gonadotropin (free β-hCG) and pregnancy associated plasma protein-A (PAPP-A) at 10 to 14 weeks of gestation which are combined to give a risk assessment and stratify women as high or low risk (Snijders et al, 1998;Spencer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In large cohorts, combined first-trimester nuchal translucency (NT) and serum analyte measurements can detect approximately 80-85% of fetuses affected by Down syndrome, a detection rate that is similar to that of second-trimester analyte screening. 1,2 Despite recommendation by the American College of Obstetricians and Gynecologists and other medical societies to universally offer first trimester screening, 3 some states have yet to incorporate first-trimester screens into government-funded aneuploidy screening programs.…”
Section: Introductionmentioning
confidence: 99%